THE EFFECT OF MEDIA GUESSING GAME TOWARDS UNIVERSITY STUDENTS’ WRITING ABILITY ON DESCRIPTIVE TEXT LOCAL TOURISM CONTENT - Irma Khoirot Daulay; Nurmahyuni Asrul (University of Kuningan, 2021)
This study aims to determine the effect of media guessing games on students’ writing ability on the descriptive text about local tourism. The type of research is quasi-experimental. The population in the research is students of University of Prima Indonesia. The samples were taken by cluster random sampling which consists of two classes namely the experimental class and the control class and each class consists of 25. The experimental group was taught by guessing game media while the control group was taught by conventional teaching media in writing descriptive text. The instruments used were test sheets for writing and observation sheets. The techniques used in analyzing the data were descriptive statistical analysis and t-test. The finding of the research explained that guessing game media of local tourism content successfully effect students’ ability in writing descriptive text, especially on local tourism conten